The relationship between mindfulness and resilience: The mediating role of self compassion and emotion regulation in a sample of underprivileged Turkish adolescents - Aydın Sünbül, Zeynep; Yerin Güneri, Oya (Pergamon-Elsevier Science Ltd, 2019)
The purpose of this study was to examine a mindfulness model of resilience through the mediating effects of self compassion and difficulties in emotion regulation among underprivileged Turkish adolescents. The sample of the study consisted of 752 students (426 female, 326 male) who aged 14-19 (M = 15.82, SD = 0.88). A path analysis was conducted in order to examine the proposed model. The results showed mindfulness to be a positive and significant predictor of self-compassion while negatively and significantly predicting difficulties in emotion regulation. Furthermore, self-compassion and difficulties in emotion regulation were found to be significant predictors of resilience. Indirect paths from mindfulness to resilience (via self-compassion and via difficulties in emotion regulation) were also significant in the model. The hypothesized model explained 21% of the variance in resilience scores.
WOS: 000456764200049
Keywords: Resilience; Mindfulness; Self-Compassion; Difficulties In Emotion Regulation; Adolescents With Low Socio-Economic Status